Photonic Crystals A Glimpse of the Current Research Trends - Kumar Choudhury, Pankaj (IntechOpen, 2019)
The role of dielectric mirrors is very important in optics. These are used for several purposes like imaging, fabricating laser cavities, and so on. The basis for the propagation of photons in dielectric mediums is the same as electrons in solid crystals. If the electrons can be diffracted by a periodic potential well, photons could also be equally well diffracted by a periodic modulation of the refractive index of the medium. This idea led to the development of many new artificial photonic materials and optical micro- and nanostructures. Since the mechanism of light guidance is essentially due to the microstructural features of the medium, a wide variety of photonic structures, e.g., photonic band-gap fibers in 1D and photonic band-gap crystals in 2D and 3D, can be realized. Photonic Crystals - A Glimpse of the Current Research Trends essentially highlights the recent developments in the arena of photonic crystal research. It is expected to be useful for expert as well as novice researchers; the former group of readers would be abreast of recent research advancements, whereas the latter group would benefit from grasping knowledge delivered by expert scientists.